Application of saline water and herbicides as a method for weed control in the tropical turfgrass: its impact on nutrient uptake and soil microbial community - Uddin, Md. Kamal; Juraimi, Abdul Shukor; Ismail, Mohd Razi; Naher, Umme Aminun; Othman, Radziah; Abdul Rahim, Anuar (Academic Journals, 2011)
A field study was conducted at Universiti Putra Malaysia with the aim to find out a suitable environment friendly weed control method for turfgrass species in combination with different levels of sea water and herbicides. A number of three turfgrass species (Paspalum vaginatum, Zoysia japonica and Cynodon dactylon 'satiri') and five associative weed species (Eragrostis atrovirens, Sporobolus diander, Cyperus aromaticus, Cyperus rotundus, and Emilia sonchifolia) were treated with different doses of sea water level and two herbicides (Trifloxysulfuron -sodium and Quinclorac). The shoot uptake of Na, K, Ca, Mg were determined as a indicator of salt tolerance using Atomic Absorption Spectrophotometer. Among the three turfgrass species C. dactylon 'satiri' had higher tissue accumulations of Na with greater reduction of K (27%), Ca (42%), and Mg (23%). The tested five weed species showed higher Na accumulation and reduction of Na, K, Ca and Mg compared to turfgrasses. The highest Na accumulation was found in E. sonchifolia and S. diander weed species. Microbial populations were found highest in control treatment. While comparing 9 treatments, the combination of 3/4 recommended herbicides, either trifloxysulfuron-sodium or quinclorac with 3/4 sea water had lower reductions of uptake of K (5 to 19%), Mg (10-37%) and Ca (21-31%) in turfgrass species and exhibited higher microbial populations, which proved suitable for turfgrass weed management. In general, it may concluded that, combination of reduced doses (3/4) of sea water and herbicide is the best method for weed control in tropical trufgrass species and also friendly to environment.